A closer look at fertilizer legislations for silage maize across selected European countries: part II–overestimation of economically optimal nitrogen rates - Josephine Bukowiecki; Larissa Ullrich; Martin Komainda; Antje Herrmann; Kurt Möller; Frank Liebisch; Johannes Isselstein; Manfred Kayser; Michael Grunert; Henning Kage; Insa Kühling (Nutrient Cycling in Agroecosystems, 2026)
Silage maize cultivation in Central Europe offers significant potential for improving nitrogen (N) efficiency, but quantifying N savings under current fertilization regulations and identifying further opportunities for improvement remain crucial. This study addresses these gaps by analyzing the influence of site-specific and management factors on the economically optimal N fertilization rate (EONR). EONR was calculated for 223 yield response functions across diverse silage maize cultivation conditions using a quadratic-plateau function, which outperformed quadratic and linear-plateau models in describing maize yield response to increasing N rates. A linear regression model was developed through a multistage analysis, incorporating only significant parameters available at the start of the growing season to estimate EONR. These EONRs, along with representative silage maize cultivation scenarios, were used to evaluate N fertilization recommendations within national frameworks. Key influences included management practices affecting plant residue quantity and carbon-to-nitrogen ratios, along with weather and soil parameters. Optimal management for silage maize following grain cereals, the predominant pre-crop in many regions, involved straw removal and frost-killed non-legume winter cover crops to maximize N saving potential. Official N fertilization recommendations exceeded calculated EONRs on average by more than 14%, with minimal correlation (R 2 < 0.1). In contrast, the developed regression model estimated EONR with a R adj 2 of 0.30, highlighting key research areas and opportunities for improving N efficiency in silage maize cultivation in Central Europe.

A closer look at fertilizer legislations for silage maize across selected European countries: part I—insufficient consideration of net nitrogen mineralization - Josephine Bukowiecki; Larissa Ullrich; Martin Komainda; Antje Herrmann; Kurt Möller; Frank Liebisch; Kiril Manevski; Emanuel Jaufmann; Michael Grunert; Henning Kage; Insa Kühling (Nutrient Cycling in Agroecosystems, 2026)
Optimizing nitrogen (N) efficiency in European silage maize cultivation requires better quantification of N savings beyond existing regulations and identifying further opportunities to enhance efficiency. This study focuses on understanding how site and management factors influence net N mineralization. A comprehensive dataset from silage maize field trials across five Central European countries was analyzed using a multistage framework to develop a linear regression equation for estimating net N mineralization during the growing season based on key parameters known before the growing season. The final regression model, with a R adj 2 of 0.38, identified ten significant variables affecting net N mineralization. Evaluation of German and French fertilization frameworks, using representative regional use cases, indicated that national guidelines may underestimate or insufficiently capture net N mineralization. Major factors influencing soil net N mineralization included management practices impacting biomass quantity and the carbon-to-N ratio of plant residues, with N fertilization showing a negative effect on net N mineralization. Weather conditions and soil clay contributed to the observed variability to a lesser extent. For silage maize following grain cereals, a predominant cropping sequence within the investigated regions, the highest net N mineralization was achieved by combining straw removal with a frost-killed non-legume cover crop, suggesting potential for reduced N fertilization without yield loss.

Beyond mobility: A prospective study on diet and metabolism in hereditary spastic paraplegia - Christina Erhardt; Imke T. Spatz; Hans J. Herrmann; Zacharias Kohl; Yurdagül Zopf; Heiko Gassner; Jürgen Winkler; Martin Regensburger (Metabolic Brain Disease, 2026)
Metabolism plays an important role in neurodegenerative diseases. Hereditary spastic paraplegias (HSP) are a heterogeneous group of rare genetic neurodegenerative disorders, commonly characterized by the clinical syndrome of progressive lower limb spasticity and mobility loss. Obesity has been linked to distinct genotypes, but the role of metabolism and nutrition in HSP remains unclear.We aimed to To evaluate metabolism and nutrition in specific HSP genotypes and to assess the impact of nutritional counseling on disease progression and body composition. In this prospective explorative pilot study, we assessed the neurological, metabolic and nutritional status of patients with HSP at baseline and one year after nutritional counseling. A total of 36 patients with genetically confirmed SPG4-, SPG7- and SPG11-associated HSP were recruited. BMI in SPG4 and SPG7 was comparable to healthy population data, whereas SPG11 showed significantly higher BMI (+ 22.9%, p < 0.05) with a considerable interindividual variability. Across all genotypes, disease severity according to the Spastic Paraplegia Rating Scale correlated negatively with leg muscle mass (ρ = -0.39, p < 0.05), protein (ρ = -0.35, p < 0.05) and fiber intake (ρ = -0.41, p < 0.05). After one year, there was a significant loss of relative muscle mass (-7.2%, p < 0.001). Progressive loss of muscle mass in HSP asks for an effective nutritional intervention combined with exercise in order to influence disease progression in HSP. The SPG11-associated obese phenotype may evolve with disease progression due to multifactorial metabolic changes, beyond reduced mobility.

Reducing tannic acid astringency with aromas - effectiveness of whisky lactone and isoamyl acetate - Alix Rollinat; Christophe Martin; Noémie Herrmann; Mélanie Lelievre; Géraldine Lucchi; Fabrice Neiers; Carole Tournier; Francis Canon (Food Chemistry, 2025)

Salix species and varieties affect the molecular composition and diversity of soil organic matter - Louis J. P. Dufour; Johanna Wetterlind; Naoise Nunan; Katell Quenea; Andong Shi; Martin Weih; Anke M. Herrmann (Plant and Soil, 2025)
Background and aims Most studies of the relationships between the composition of soil organic matter and plant cover have been carried out at the plant genera level. However, they have largely overlooked the potential effects that plant varieties, belonging to the same genus, can have on soil organic matter. Methods We investigated whether plant varieties belonging to different Salix species ( S. dasyclados and S. viminalis) impacted the composition of organic matter using mid-infrared spectroscopy and pyrolysis GC/MS. Top-soils were taken from an 18 year-old long-term field trial where six Salix varieties were grown as short-rotation coppice under two fertilisation regimes. Results Significant differences in the molecular composition and diversity of the soil organic matter were observed in the fertilised plots. The effects were mostly visible at the species level, i.e. the organic matter in soil under S. dasyclados varieties had higher molecular diversity and lignin content than under S. viminalis , potentially due to differences in the amount and composition of their litter inputs. Smaller differences among varieties from the same species were also observed. No significant effects of Salix varieties were observed in the unfertilised plots. The relatively high degree of spatial variability of several soil properties found in these plots may have masked plant variety and/or species effects. Conclusion This study provides evidence that the identity of Salix species or varieties can affect the molecular composition and diversity of soil organic matter. The corresponding traits should be considered in breeding programmes to enhance soil organic C accumulation and persistence.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

UAV-based canopy monitoring: calibration of a multispectral sensor for green area index and nitrogen uptake across several crops - Josephine Bukowiecki; Till Rose; Katja Holzhauser; Steffen Rothardt; Maren Rose; Martin Komainda; Antje Herrmann; Henning Kage (Precision Agriculture, 2024)
The fast and accurate provision of within-season data of green area index ( GAI ) and total N uptake ( total N ) is the basis for crop modeling and precision agriculture. However, due to rapid advancements in multispectral sensors and the high sampling effort, there is currently no existing reference work for the calibration of one UAV (unmanned aerial vehicle)-based multispectral sensor to GAI and total N for silage maize, winter barley, winter oilseed rape, and winter wheat. In this paper, a practicable calibration framework is presented. On the basis of a multi-year dataset, crop-specific models are calibrated for the UAV-based estimation of GAI throughout the entire growing season and of total N until flowering. These models demonstrate high accuracies in an independent evaluation over multiple growing seasons and trial sites (mean absolute error of 0.19–0.48 m 2 m −2 for GAI and of 0.80–1.21 g m −2 for total N ). The calibration of a uniform GAI model does not provide convincing results. Near infrared-based ratios are identified as the most important component for all calibrations. To account for the significant changes in the GAI / total N ratio during the vegetative phase of winter barley and winter oilseed rape, their calibrations for total N must include a corresponding factor. The effectiveness of the calibrations is demonstrated using three years of data from an extensive field trial. High correlation of the derived total N uptake until flowering and the whole-season radiation uptake with yield data underline the applicability of UAV-based crop monitoring for agricultural applications.

COVID-19 in Systemic Lupus Erythematosus patients treated with belimumab: a retrospective clinical study - Yinlan Wu; Yanhong Li; Tong Wu; Deying Huang; Jianhong Wu; Weihua Zhang; Xuejun Jiang; Chaoqiong Yao; Xiuping Liang; Lu Cheng; Zehui Liao; Fang Xu; et al. (Immunologic Research, 2024)

No effect on biological or chemical soil properties when amended with effective microorganisms for improved cover crop decomposition - Simon Oberholzer; Christa Herrmann; Natacha Bodenhausen; Hans-Martin Krause; Adrien Mestrot; Chinwe Ifejika Speranza; Klaus A. Jarosch (Applied Soil Ecology, 2024)

Seasonal variations of microplastic pollution in the German River Weser - Sonya R. Moses; Martin G.J. Löder; Frank Herrmann; Christian Laforsch (Science of The Total Environment, 2023)

Aircraft noise exposure and risk for recurrent cardiovascular events after acute coronary syndrome: A prospective patient cohort study - Hans-Georg Olbrich; Martin Röösli; Eva Herrmann; Christian Maschke; Kerstin Schadow; Torsten Hähnel; Hans-Jürgen Rupprecht; Martin Kaltenbach (Environmental Research, 2023)

Isotope diffusion and re-equilibration of copper and evaporation of mercury during weathering of tetrahedrite in an oxidation zone - Juraj Majzlan; Julia Herrmann; Martin Števko; Jan G. Wiederhold; Marina Lazarov; Rastislav Milovský (Geochemistry, 2023)

Aqueous-phase photo-oxidation of selected green leaf volatiles initiated by OH radicals: Products and atmospheric implications - Kumar Sarang; Tobias Otto; Sahir Gagan; Krzysztof Rudzinski; Thomas Schaefer; Martin Brüggemann; Irena Grgić; Adam Kubas; Hartmut Herrmann; Rafal Szmigielski (Science of The Total Environment, 2023)

Genetic mapping of the powdery mildew resistance gene Pm7 on oat chromosome 5D - Sophie Brodführer; Volker Mohler; Melanie Stadlmeier; Sylwia Okoń; Steffen Beuch; Martin Mascher; Nicholas A. Tinker; Wubishet A. Bekele; Bernd Hackauf; Matthias Heinrich Herrmann (Theoretical and Applied Genetics, 2023)
Key message Three independent experiments with different genetic backgrounds mapped the resistance gene Pm7 in the oat genome to the distal part of the long arm of chromosome 5D. Abstract Resistance of oat to Blumeria graminis DC. f. sp. avenae is an important breeding goal in Central and Western Europe. In this study, the position of the effective and widely used resistance gene Pm7 in the oat genome was determined based on three independent experiments with different genetic backgrounds: genome-wide association mapping in a diverse set of inbred oat lines and binary phenotype mapping in two bi-parental populations. Powdery mildew resistance was assessed in the field as well as by detached leaf tests in the laboratory. Genotyping-by-sequencing was conducted to establish comprehensive genetic fingerprints for subsequent genetic mapping experiments. All three mapping approaches located the gene to the distal part of the long arm of chromosome 5D in the hexaploid oat genome sequences of OT3098 and ‘Sang.’ Markers from this region were homologous to a region of chromosome 2Ce of the C-genome species, Avena eriantha , the donor of Pm7 , which appears to be the ancestral source of a translocated region on the hexaploid chromosome 5D.

Citizen science’s transformative impact on science, citizen empowerment and socio-political processes - Julia von Gönner; Thora M. Herrmann; Till Bruckermann; Michael Eichinger; Susanne Hecker; Friederike Klan; Julia Lorke; Anett Richter; Ulrike Sturm; Silke Voigt-Heucke; Wiebke Brink; Christin Liedtke; et al. (Socio-Ecological Practice Research, 2023)
Citizen science (CS) can foster transformative impact for science, citizen empowerment and socio-political processes. To unleash this impact, a clearer understanding of its current status and challenges for its development is needed. Using quantitative indicators developed in a collaborative stakeholder process, our study provides a comprehensive overview of the current status of CS in Germany, Austria and Switzerland. Our online survey with 340 responses focused on CS impact through (1) scientific practices, (2) participant learning and empowerment, and (3) socio-political processes. With regard to scientific impact, we found that data quality control is an established component of CS practice, while publication of CS data and results has not yet been achieved by all project coordinators (55%). Key benefits for citizen scientists were the experience of collective impact (“making a difference together with others”) as well as gaining new knowledge. For the citizen scientists’ learning outcomes, different forms of social learning, such as systematic feedback or personal mentoring, were essential. While the majority of respondents attributed an important value to CS for decision-making, only few were confident that CS data were indeed utilized as evidence by decision-makers. Based on these results, we recommend (1) that project coordinators and researchers strengthen scientific impact by fostering data management and publications, (2) that project coordinators and citizen scientists enhance participant impact by promoting social learning opportunities and (3) that project initiators and CS networks foster socio-political impact through early engagement with decision-makers and alignment with ongoing policy processes. In this way, CS can evolve its transformative impact.

Human Coxsackie- and adenovirus receptor is a putative target of neutrophil elastase-mediated shedding - Leonie Herrmann; Louise Schelletter; Raimund Hoffrogge; Karsten Niehaus; Volker Rudolph; Martin Farr (Molecular Biology Reports, 2022)
Background During viral-induced myocarditis, immune cells migrate towards the site of infection and secrete proteases, which in turn can act as sheddases by cleaving extracellular domains of transmembrane proteins. We were interested in the shedding of the Coxsackie- and adenovirus receptor (CAR) that acts as an entry receptor for both eponymous viruses, which cause myocarditis. CAR shedding by secreted immune proteases could result in a favourable outcome of myocarditis as CAR’s extracellular domain would be removed from the cardiomyocytes’ surface leading to decreased susceptibility to ongoing viral infections. Methods and results In this work, matrix metalloproteinases and serine proteinases were screened for their proteolytic activity towards human CAR. Whereas matrix metalloproteinases, proteinase 3, and cathepsin G did not cleave human recombinant CAR or only within long incubation times, neutrophil elastase showed a distinct cleavage pattern of CAR’s extracellular domain that was time- and dose-dependent. Neutrophil elastase cleaves CAR at its membrane-proximal immunoglobulin domain as we determined by nanoLC-MS/MS. Furthermore, neutrophil elastase treatment of cells reduced CAR surface levels as seen by flow cytometry and immunofluorescence microscopy. Conclusions With this study, we show that CAR might be a target for shedding by neutrophil elastase.

Optical clock technologies for global navigation satellite systems - Thilo Schuldt; Martin Gohlke; Markus Oswald; Jan Wüst; Tim Blomberg; Klaus Döringshoff; Ahmad Bawamia; Andreas Wicht; Matthias Lezius; Kai Voss; Markus Krutzik; Sven Herrmann; et al. (GPS Solutions, 2021)
Future generations of global navigation satellite systems (GNSSs) can benefit from optical technologies. Especially optical clocks could back-up or replace the currently used microwave clocks, having the potential to improve GNSS position determination enabled by their lower frequency instabilities. Furthermore, optical clock technologies—in combination with optical inter-satellite links—enable new GNSS architectures, e.g., by synchronization of distant optical frequency references within the constellation using time and frequency transfer techniques. Optical frequency references based on Doppler-free spectroscopy of molecular iodine are seen as a promising candidate for a future GNSS optical clock. Compact and ruggedized setups have been developed, showing frequency instabilities at the 10 –15 level for averaging times between 1 s and 10,000 s. We introduce optical clock technologies for applications in future GNSS and present the current status of our developments of iodine-based optical frequency references.

Composition and compound proportions affect the response to complex chemical signals in a spiny lizard - Cristina Romero-Diaz; Stephanie M. Campos; Morgan A. Herrmann; Helena A. Soini; Milos V. Novotny; Diana K. Hews; Emília P. Martins (Behavioral Ecology and Sociobiology, 2021)

A mobile DNA laboratory for forensic science adapted to coronavirus SARS-CoV-2 diagnosis - Patrick Touron; Christian Siatka; Amaury Pussiau; Sébastien Follot; Thibaud Fritz; Mikaël Petit; Noussair Latifa; Jean-Louis Herrmann; Martin Rottman; Antoinette Lemoine; Sylvain Hubac (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Length Polymorphisms in the Angiotensin I-Converting Enzyme Gene and the Serotonin-Transporter-Linked Polymorphic Region Constitute a Risk Haplotype for Depression in Patients with Coronary Artery Disease - Thomas Meyer; Isabel Rothe; Julia Staab; Hans-Christian Deter; Stella V. Fangauf; Stefanie Hamacher; Martin Hellmich; Jana Jünger; Karl-Heinz Ladwig; Matthias Michal; Katja Petrowski; Joram Ronel; et al. (Biochemical Genetics, 2020)
Genetic variations affecting the course of depressive symptoms in patients with coronary artery disease (CAD) have not yet been well studied. Therefore, we set out to investigate whether distinct haplotypes of the two insertion/deletion polymorphisms in the serotonin-transporter-linked polymorphic region ( 5-HTTLPR ) and the angiotensin I-converting enzyme ( ACE ) gene located on chromosome 17 can be identified as risk factors for trajectories of depression. Clinical and genotyping data were derived from 507 depressed CAD patients participating in the randomized, controlled, multicenter Stepwise Psychotherapy Intervention for Reducing Risk in Coronary Artery Disease (SPIRR-CAD) trial, of whom the majority had an acute cardiac event before study inclusion. Depression scores on the Hospital Anxiety and Depression Scale (HADS) were assessed at baseline and at five follow-up time points up to 2 years after study entrance. At baseline, depression scores did not significantly differ between patients carrying the risk haplotype ACE D/D, 5-HTTLPR I/I ( n = 46) and the non-risk haplotypes ( n = 461, 10.9 ± 2.7 versus 10.4 ± 2.5, p = 0.254). HADS-depression scores declined from study inclusion during the first year irrespective of the genotype. At each follow-up time point, HADS-depression scores were significantly higher in ACE D/D, 5-HTTLPR I/I carriers than in their counterparts. Two years after study inclusion, the mean HADS depression score remained 1.8 points higher in patients with the risk haplotype as compared to subjects not carrying this haplotype (9.9 ± 4.2 versus 8.1 ± 4.0, p = 0.009). In summary, the presence of the ACE D/D, 5-HTTLPR I/I haplotype may be a vulnerability factor for comorbid depressive symptoms in CAD patients.

Towards a pro-resolving concept in systemic lupus erythematosus - Sebastian Boeltz; Melanie Hagen; Jasmin Knopf; Aparna Mahajan; Maximilian Schick; Yi Zhao; Cornelia Erfurt-Berge; Jürgen Rech; Luis E. Muñoz; Martin Herrmann (Seminars in Immunopathology, 2019)

Reduced spontaneous low frequency oscillations as measured with functional near-infrared spectroscopy in mild cognitive impairment - Julia B. M. Zeller; Andrea Katzorke; Laura D. Müller; Judith Breunig; Florian B. Haeussinger; Jürgen Deckert; Bodo Warrings; Martin Lauer; Thomas Polak; Martin J. Herrmann (Brain Imaging and Behavior, 2019)

Effects of catch crops on silage maize (Zea mays L.): yield, nitrogen uptake efficiency and losses - Martin Komainda; Friedhelm Taube; Christof Kluß; Antje Herrmann (Nutrient Cycling in Agroecosystems, 2018)

The Ocean's Vital Skin: Toward an Integrated Understanding of the Sea Surface Microlayer - Anja Engel; Hermann W. Bange; Michael Cunliffe; Susannah M. Burrows; Gernot Friedrichs; Luisa Galgani; Hartmut Herrmann; Norbert Hertkorn; Martin Johnson; Peter S. Liss; Patricia K. Quinn; Markus Schartau; et al. (Frontiers in Marine Science, 2017)

HIV-1 replication in central nervous system increases over time on only protease inhibitor therapy - Maximilian Donath; Timo Wolf; Martin Stürmer; Eva Herrmann; Markus Bickel; Pavel Khaykin; Siri Göpel; Peter Gute; Annette Haberl; Philipp de Leuw; Gundolf Schüttfort; Annemarie Berger; et al. (Medical Microbiology and Immunology, 2016)

Prevalence of K65R in patients treated with tenofovir disoproxil fumarate: recommendations based on the Frankfurt HIV Cohort Study Resistance Database (FHCS-RD) - Claudia Reinheimer; Anna Wesner; Oliver T. Keppler; Hans Wilhelm Doerr; Eva Herrmann; Martin Stürmer; Christoph Stephan (Medical Microbiology and Immunology, 2016)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

The effects of Kv1.3 and IKCa1 channel inhibition on cytokine production and calcium influx of T lymphocytes in rheumatoid arthritis and ankylosing spondylitis - Gergely Toldi; Luis Munoz; Martin Herrmann; Georg Schett; Attila Balog (Immunologic Research, 2016)

Modulating bilayer mechanical properties to promote the coupled folding and insertion of an integral membrane protein - Michaela Herrmann; Bartholomäus Danielczak; Martin Textor; Jessica Klement; Sandro Keller (European Biophysics Journal, 2015)

Quantification of Climate Change Impact on Regional Agricultural Irrigation and Groundwater Demand - Peter Kreins; Martin Henseler; Jano Anter; Frank Herrmann; Frank Wendland (Water Resources Management, 2015)

How neutrophil extracellular traps orchestrate the local immune response in gout - Christian Maueröder; Deborah Kienhöfer; Jonas Hahn; Christine Schauer; Bernhard Manger; Georg Schett; Martin Herrmann; Markus H Hoffmann (Journal of Molecular Medicine, 2015)

Multilevel impact of the dopamine system on the emotion-potentiated startle reflex - Katharina Domschke; Bernward Winter; Agnieszka Gajewska; Stefan Unterecker; Bodo Warrings; Andrea Dlugos; Swantje Notzon; Kathrin Nienhaus; Falko Markulin; Astrid Gieselmann; Christian Jacob; Martin J. Herrmann; et al. (Psychopharmacology, 2015)

Enabling optimization in LCA: from “ad hoc” to “structural” LCA approach—based on a biodiesel well-to-wheel case study - Ivan T. Herrmann; Martin Lundberg-Jensen; Andreas Jørgensen; Thomas Stidsen; Henrik Spliid; Michael Hauschild (The International Journal of Life Cycle Assessment, 2014)

Impact of HIV-1 replication on immunological evolution during long-term dual-boosted protease inhibitor therapy - Christoph Stephan; Valentin Bartha; Eva Herrmann; Nils von Hentig; Pavel Khaykin; Gaby Knecht; Peter Gute; Hans-Reinhard Brodt; Martin Stürmer; Annemarie Berger; Markus Bickel (Medical Microbiology and Immunology, 2013)

New tools for assessing the individual risk of metastasis in renal cell carcinoma - Edwin Herrmann; Carsten Weishaupt; Birgit Pöppelmann; Carina Hillgruber; Gerald Pühse; Laura Maria Krabbe; Micha Feld; Martin Steinhoff; Tobias Goerge (Clinical & Experimental Metastasis, 2013)

Modification of caffeine effects on the affect-modulated startle by neuropeptide S receptor gene variation - Katharina Domschke; Benedikt Klauke; Bernward Winter; Agnes Gajewska; Martin J. Herrmann; Bodo Warrings; Andreas Mühlberger; Katherina Wosnitza; Andrea Dlugos; Swantje Naunin; Kathrin Nienhaus; Manfred Fobker; et al. (Psychopharmacology, 2012)

The role of APP and APLP for synaptic transmission, plasticity, and network function: lessons from genetic mouse models - Martin Korte; Ulrike Herrmann; Xiaomin Zhang; Andreas Draguhn (Experimental Brain Research, 2012)

Modified light use efficiency model for assessment of carbon sequestration in grasslands of Kazakhstan: combining ground biomass data and remote-sensing - Pavel A. Propastin; Martin W. Kappas; Stefanie M. Herrmann; Compton J. Tucker (International Journal of Remote Sensing, 2012)

Differential effects of habitat isolation and landscape composition on wasps, bees, and their enemies - Christof Schüepp; John D. Herrmann; Felix Herzog; Martin H. Schmidt-Entling (Oecologia, 2011)

Inefficient clearance of dying cells in patients with SLE: anti-dsDNA autoantibodies, MFG-E8, HMGB-1 and other players - Kristin Kruse; Christina Janko; Vilma Urbonaviciute; Claudia T. Mierke; Thomas H. Winkler; Reinhard E. Voll; Georg Schett; Luis E. Muñoz; Martin Herrmann (Apoptosis, 2010)

Dangerous attraction: phagocyte recruitment and danger signals of apoptotic and necrotic cells - Christoph Peter; Sebastian Wesselborg; Martin Herrmann; Kirsten Lauber (Apoptosis, 2010)

Pre-attentive Spectro-temporal Feature Processing in the Human Auditory System - Tino Zaehle; Lutz Jancke; Christoph S. Herrmann; Martin Meyer (Brain Topography, 2009)

Variation along the shy–bold continuum in extremophile fishes (Poecilia mexicana, Poecilia sulphuraria) - Rüdiger Riesch; Virginia Duwe; Nina Herrmann; Lisa Padur; Annemarie Ramm; Kristin Scharnweber; Matthias Schulte; Tanja Schulz-Mirbach; Madlen Ziege; Martin Plath (Behavioral Ecology and Sociobiology, 2009)

MK801- and scopolamine-induced amnesias are reversed by an Amazonian herbal locally used as a “brain tonic” - Adriana Lourenço da Silva; Bárbara da Silva Martins; Viviane de Moura Linck; Ana Paula Herrmann; Nathalia Mai; Domingos S. Nunes; Elaine Elisabetsky (Psychopharmacology, 2009)

Hypothesis: human serum-borne albumin bound lipids promote cellular survival after apoptosis induction by a variety of stimuli - Martin Schiller; Sandra Franz; Petra Heyder; Reinhard E. Voll; Udo S. Gaipl; Hanns-Martin Lorenz; Joachim R. Kalden; Martin Herrmann (Apoptosis, 2008)

Polymorphisms in 33 inflammatory genes and risk of myocardial infarction—a system genetics approach - Sandrine Barbaux; David-Alexandre Tregouet; Viviane Nicaud; Odette Poirier; Claire Perret; Tiphaine Godefroy; Carole Francomme; Christophe Combadiere; Dominique Arveiler; Gerald Luc; Jean-Bernard Ruidavets; Alun E. Evans; et al. (Journal of Molecular Medicine, 2007)

Transcriptional changes in two types of pre-mycorrhizal roots and in ectomycorrhizas of oak microcuttings inoculated with Piloderma croceum - Patrick Frettinger; Jérémy Derory; Sylvie Herrmann; Christophe Plomion; Frédéric Lapeyrie; Ralf Oelmüller; Francis Martin; François Buscot (Planta, 2006)

Source Localization of Early Stages of Face Processing - Martin J. Herrmann; Ann-Christine Ehlis; Andreas Muehlberger; Andreas J. Fallgatter (Brain Topography, 2005)

Iron overload in adult Hfe-deficient mice independent of changes in the steady-state expression of the duodenal iron transporters DMT1 and Ireg1/ferroportin - Thomas Herrmann; Martina Muckenthaler; Frank van der Hoeven; Karen Brennan; Sven G. Gehrke; Nadia Hubert; Consolato Sergi; Hermann-Josef Gröne; Iris Kaiser; Isabella Gosch; Martin Volkmann; Hans-Dieter Riedel; et al. (Journal of Molecular Medicine, 2004)

Effect of inherent epileptic seizures on brain injury after transient cerebral ischemia in Mongolian gerbils - Martina Herrmann; Martin Stern; Florence Vollenweider; Cordula Nitsch (Experimental Brain Research, 2004)

Studying genotype-phenotype relationships: cardiovascular disease as an example - Stefan-Martin Herrmann; Martin Paul (Journal of Molecular Medicine, 2002)

Polymorphisms in the genes encoding platelet-derived growth factor A and α receptor - Stefan-Martin Herrmann; Sylvain Ricard; Viviane Nicaud; Eva Brand; Isabelle Behague; Hervé Blanc; Jean-Bernard Ruidavets; Alun Evans; Dominique Arveiler; Gérald Luc; Odette Poirier; François Cambien (Journal of Molecular Medicine, 2000)

Stability of Late Event-Related Potentials: Topographical Descriptors of Motor Control Compared with the P300 Amplitude - Andreas J. Fallgatter; Sabine S. Eisenack; Barbara Neuhauser; Derlis Aranda; Peter Scheuerpflug; Martin J. Herrmann (Brain Topography, 2000)

Regulation of Photosystem II core protein phosphorylation at the substrate level: Light induces exposure of the CP43 chlorophyll a protein complex to thylakoid protein kinase(s) - Martin Vink; Hagit Zer; Reinhold G. Herrmann; Bertil Andersson; Itzhak Ohad (Photosynthesis Research, 2000)

Identification of two polymorphisms in the early growth response protein-1 gene: possible association with lipid variables - Eva Brand; Stefan-Martin Herrmann; Viviane Nicaud; Alun Evans; Jean-Bernard Ruidavets; Dominique Arveiler; Gerald Luc; François Cambien; Florent Soubrier (Journal of Molecular Medicine, 2000)